Sustained Delivery of IL-1Ra from PF127-Gel Reduces Hyperglycemia in Diabetic GK-Rats - Akash, Muhammad Sajid Hamid; Rehman, Kanwal; Sun, Hongying; Chen, Shuqing (PLOS ONE, 2013)
Interleukin-1beta (IL-1β) is a major cause for induction of various inflammatory mechanisms that are decisively involved to provoke pathogenesis of type 2 diabetes mellitus (T2DM). Interleukin-1 receptor antagonist (IL-1Ra) a naturally occurring anti-inflammatory antagonist of IL-1β has been recently approved for treatment of T2DM but due to its short half-life, higher doses and frequent dosing intervals are required. Pluronic F-127 (PF127) has previously shown to prolong the release of various proteinous drugs and their serum half-lives. Subsequently, in our previous work, we developed a new dosage form of IL-1Ra using PF127 and investigated its in-vitro and in-vivo effects. Here in present work, we have extended this approach using diabetic Goto-kakizaki (GK) rats. We administered IL-1Ra loaded in PF127 gel subcutaneously for one month into GK rats. IL-1Ra loaded in PF127 gel exhibited a sustained and prolonged hypoglycemic effects on treated animals. Intraperitoneal glucose tolerance test (IPGTT) results showed that IL-1Ra loaded in PF127 gel increased glucose tolerance along with increased insulin sensitivity and β-cell’s secretory function in treated rats. Moreover, significant reduction in pro-insulin/insulin ratio, lipid profiles and interleukin 6 (IL-6) were also observed. Immunohistochemical analysis showed slight macrophages infiltration in pancreatic islets. Histochemical analysis revealed no PF127-induced alteration in the normal physiology of skin and kidney of treated animals. Hence, we concluded that IL-1Ra loaded in PF127 gel has potential to exhibit broad spectrum anti-inflammatory effects alleviating the symptoms of T2DM.